Design of Broadband High Gain Polarization Reconfigurable Fabry-Perot Cavity Antenna Using Metasurface - Ni, Chun; Liu, Changqing; Zhang, Zhongxiang; Chen, Mingsheng; Zhang, Liang; Wu, Xianliang (Frontiers in Physics, 2020)
A broadband high gain polarization reconfigurable antenna based on metasurface has been presented. The antenna is composed of a planar metasurface, a slot antenna and an air cavity. The metasurface is made up of 64 identical patches, and all the patches are on the top surface of the substrate. The spatial equivalent circuit of the metasurface is discussed and two approximate calculation formulas of the equivalent circuit are obtained. The antenna can be reconfigured to linear polarization, left-hand and right-hand circular polarizations by adjusting the relative positions between the metasurface and the planar slot antenna. The gain of the antenna is improved. In order to verify these methods, the antenna is studied and designed to operate at around 11GHz. The simulated and measured results show that the 3dB axis ratio bandwidth is 10-12GHz (fractional bandwidth 18.18%) and maximum gain of 14.6dBi.